Analisis Faktor-Faktor yang Mempengaruhi Persistensi Laba Dengan Kepemilikan Institusional Sebagai Variabel Moderating Pada Perusahaan LQ 45 Yang Terdaftar Di Bursa Efek Indonesia - CH, Flourien Nurul; Miranti, Miranti; Rusli, Devvy; Supriati, Diana (JURNAL ONLINE INSAN AKUNTAN, 2025)
This research aims (1) To analyze the effect of operating cash flow on profit persistence in LQ45 companies listed on the Indonesia Stock Exchange (BEI), (2) To analyze the effect of leverage on profit persistence in LQ45 companies listed on the stock exchange. Indonesian Stock Exchange (BEI), (3) To analyze the Influence of Book Tax Difference on Profit Persistence in LQ45 Companies Listed on the Indonesian Stock Exchange (BEI) and (4) To analyze the role of Institutional Ownership in moderating the Influence between Operating Cash Flow, Leverage, Book Tax Difference in Profit Persistence in LQ45 Companies Listed on the Indonesia Stock Exchange (BEI). This research uses quantitative descriptive methods and data collection techniques through documentation methods, namely data collection by collecting secondary data from annual financial reports that have been published on the IDX via www.idx.co.id. The data used are Operating Cash Flow, Leverage, Book Tax Difference, Profit Persistence and Institutional Ownership. The results of this research are (1) Operating Cash flow has a positive effect on earnings persistence. (2) Leverage has no effect on earnings persistence. (3) Book Tax Difference has no effect on earnings persistence. (4) Institutional Ownership is unable to moderate the influence of operating cash flow, leverage and book tax difference on earnings persistence.   Keywords : Operating Cash Flow, Leverage, Book Tax Difference, Profit Persistence Institutional Ownership